ADOPSI FINANCIAL TECHNOLOGY PADA UMKM DESA LERAN: PELUANG DAN HAMBATAN DALAM PENGUATAN KEUANGAN DIGITAL - Selmitha Dwi Pradestia; Henny Sri Astuty (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are crucial for rural economic development and social welfare. Fintech enables companies to transform transactions and channel financing, and promote financial inclusion through the use of digital finance. However, the level of fintech utilization by MSMEs in rural areas still faces various obstacles. This study examines the adoption of fintech by MSMEs in Leran Village, Palang District, Tuban Regency and the obstacles encountered. Local business owners were interviewed, observed, and documented for the study. Data shows that most MSMEs started with conventional transaction systems and then switched to fintech. Fintech can simplify transaction procedures and help business owners record and manage funds more effectively. Due to limited digital literacy among business owners, security concerns, and the continued dominance of cash transactions, fintech adoption remains minimal. This data suggests that fintech can improve business efficiency and MSME financial services. Therefore, the government, financial institutions, and fintech providers should promote digital literacy and access to digital finance to increase MSME financial inclusion. Keywords : Digital Finance; Financial Inclusion; Fintech; MSMES